The adoption of "like" and "not like" usage by Saudi international students at a US university - Khalid Ahmad Siddiq (Indonesian JELT, 2017)
Language change has been a very natural phenomenon throughout the history. Languages adapt, acquire, add, or ultimately quite sadly they extinct. In current study’s case, language user acquired, adapt, add features from the source if they spent time and interact with the native speakers of a language and L2 speaker while immersed in the target language culture and linguistic environment. Therefore, it is inevitable to ignore the native feature acquisition process. The current study primarily aimed to look into the adoption and usage of English particle like as a discourse or pragmatic marker by Saudi female students at an American university in the United States. The results show that the length of the participants stay in the US and the amount of interaction with the American English users have largely influenced their usage of loose language and gap-filler “like” in their spoken English.